Lost in time : a neurophilosophical quest to understand the perception of time in MCI patients - Coelho, Sara Cunha Leal Rocha, 1985- (2017)
Tese de doutoramento, Ciências Biomédicas (Neurociências), Universidade de Lisboa, Faculdade de Medicina, 2017